IDNLearn.com is the place where your questions are met with thoughtful and precise answers. Join our knowledgeable community to find the answers you need for any topic or issue.
Answer:
(2, - 3 )
Step-by-step explanation:
x + 4y = - 10 → (1)
2x - y = 7 → (2)
multiplying (2) by 4 and adding to (1) will eliminate y
8x - 4y = 28 → (3)
add (1) and (3) term by term to eliminate y
9x + 0 = 18
9x = 18 ( divide both sides by 9 )
x = 2
substitute x = 2 into either of the 2 equations and solve for y
substituting into (1)
2 + 4y = - 10 ( subtract 2 from both sides )
4y = - 12 ( divide both sides by 4 )
y = - 3
solution is (2, - 3 )